Synthesis of Organic Dyes with Linkers Between 9,9-Dimethylfluorenyl Terminal and alpha-Cyanoacrylic Acid Anchor, Effect of the Linkers on UV-Vis Absorption Spectra, and Photovoltaic Properties in Dye-Sensitized Solar Cells - Lee, Min-Woo; Cha, Su-Bong; Yang, Su-Jin; Park, Se Woong; Kim, Kyungkon; Park, Nam-Gyu; Lee, Duck-Hyung (WILEY-V C H VERLAG GMBH, 2009)
Six metal-free organic dyes having thiophene (1), benzene-thiophene (2). thiopliene-benzenc (3), thiophene-pyridine (4), thiophene-thiophene (5), and pyridine (6) linkers between 9,9-dimethylfluorenyl terminal group and alpha-cyanoacrylic acid anchor were synthesized. Among them, organic dye 5 showed the longest lambda(max) value (424 nm) in UV-Vis absorption spectrum, better incident monochromatic photon-to-current conversion efficiency (PCE), highest short circuit photocurrent density (J(SC) 9.33 mA(2)/Cm-2) and highest overall conversion efficiency (eta, 3.91%).
Keywords: CONVERSION EFFICIENCY; MEROCYANINE DYES; COUMARIN DYES; DESIGN; MOIETY